(untitled) (REMUNOM, 2025)
Starting from the observation that evaluations and technical expert reports still receive little emphasis in the training of civil engineers, this study aimed to analyze the perceptions, challenges, and opportunities related to the professional practice in this area among students from the 8th semester onward in Civil Engineering programs at higher education institutions in João Monlevade, Minas Gerais. To achieve this, an applied research study was conducted, adopting a quantitative approach with an exploratory-descriptive design. The technical procedure involved data collection through a structured questionnaire directed at students from the studied institutions. The results showed that despite a consensus on the importance of technical expert reports for ensuring fair decisions and professional valuation, there remains a gap between academic training and market demands—especially regarding the absence of specific courses, low participation in extracurricular activities, and perceived deficiencies in technical, ethical, and legal knowledge. Thus, this research highlights the need for greater integration between undergraduate curricula and contemporary sector demands, and suggests strengthening content and practical experiences related to expert reports in civil engineering education.